# Can someone please help me?\$15660x2/3x1/2=5220.(\$15660-5220)x2/3=6960.I have this part figured out, but I need an answer to the next part.(\$15660-answer)x2/3=answer. (\$15660-answer)-600=answer.I...

Can someone please help me?
\$15660x2/3x1/2=5220.
(\$15660-5220)x2/3=6960.
I have this part figured out, but I need an answer to the next part.

(\$15660-answer)x2/3=answer.

(\$15660-answer)-600=answer.
I need this part figured out, because I got the first part figured out.

Asked on by linnie4352

### 1 Answer|Add Yours

william1941 | College Teacher | (Level 3) Valedictorian

Posted on

Your question is quite vague as there can be several answers and they all would be right.

We are given the equation: (\$15660 -5220) x 2/3 = 6960

Let's use this to determine: (\$15660 - answer) – 600 = answer

Now (\$15660-5220) x 2/3 = 6960

=> (\$15660 - 5220) = 6960 x (3/2)

=> (\$15660 - 5220) = 10440

=> (\$15660 - 5220) - 600 = 10440 - 600

=> (\$15660 - 5220) - 600 = 9840

Therefore we get (\$15660 - 5220) - 600 = 9840

We’ve answered 320,039 questions. We can answer yours, too.